2003
DOI: 10.1128/jcm.41.8.3548-3558.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Cases of Lung Infection in Cystic Fibrosis Patients: 16S Ribosomal DNA (rDNA) Length Heterogeneity PCR and 16S rDNA Terminal Restriction Fragment Length Polymorphism Profiling

Abstract: The leading cause of morbidity and mortality in cystic fibrosis (CF) patients stems from repeated bacterial respiratory infections. Many bacterial species have been cultured from CF specimens and so are associated with lung disease. Despite this, much remains to be determined. In the present study, we characterized without prior cultivation the total bacterial community present in specimens taken from adult CF patients, extracting DNA directly from 14 bronchoscopy or sputum samples. Bacterial 16S ribosomal DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
214
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 45 publications
7
214
0
Order By: Relevance
“…This and previous studies show that the sequence-based molecular approach to clinical microbiology provides microbiological perspective that can significantly enhance the standard clinical culture-based view (16)(17)(18)(19). The use of sequences for identification in this study is a substantial improvement over electrophoretic patterns for the identification of microbes, because there is no ambiguity in identity.…”
Section: Discussionmentioning
confidence: 84%
“…This and previous studies show that the sequence-based molecular approach to clinical microbiology provides microbiological perspective that can significantly enhance the standard clinical culture-based view (16)(17)(18)(19). The use of sequences for identification in this study is a substantial improvement over electrophoretic patterns for the identification of microbes, because there is no ambiguity in identity.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies place diversity higher, with an average of 5.4 bacterial species per chronic wound [36]. Such degrees of species diversity are also observed in the CF lung, resulting from the diverse microenvironments that arise [97][98][99][100]. Conversely, Kirketerp-Moller and colleagues (2008) [5] struggled to identify multiple species during a venous leg ulcer study, highlighting the diversity and complexity of different types of chronic infection.…”
Section: In Vivo Investigation Of Biofilmsmentioning
confidence: 99%
“…Conventional diagnostic microbiology focuses on the detection of a limited group of species, including those listed above (16). However, more recent studies have indicated that the range of bacterial species harbored in sputa from adult CF patients is much wider (28,29,31). These findings emerged through the application of culture-independent analytical strategies that detect bacterial species signatures in nucleic acids extracted directly from clinical samples.…”
mentioning
confidence: 99%